ACHIEVEMENTS OF THE SADF 1961 - 1982 - Conradie, D. (Scientia Militaria - South African Journal of Military Studies, 2012)
The founding of the Republic of South Africa in May 1961 had, according to International Law, no significant implications for existing international military agreements such as the Simonstown Agreement. However, with South Africa no longer a member of the Commonwealth, certain aspects did change, egothe erection of radar stations by the RSA in High Commission Territories had to be abandoned.